A method to study sustained antimicrobial activity of rinse and dentifrice components on biofilm viability in vivo - H. C. van der Mei (Blackwell Synergy, 2006)
Aim: To develop an improved method for quantitative assessment of antimicrobial efficacy and substantivity of mouth rinses and dentifrices on in vivo treated plaque. Material and Methods: Nine- and 72-h-old plaques were formed in volunteers carrying out standardized hygiene using NaF-containing dentifrice. Plaques were collected before (baseline) in vivo treatment with dentifrices or chlorhexidine mouth rinse, immediately post-treatment and after 1 or 6 h, dispersed in demineralized water and stained with live/dead stain after which bacteria were enumerated. Dispersed baseline plaques were treated with dentifrices or chlorhexidine to determine antimicrobial efficacy against planktonic bacteria. Results: Baseline plaques revealed 56–41% viable organisms in 9- and 72-h-old plaques, respectively. Treatment of planktonic (dispersed baseline plaque) bacteria resulted in 1–4% viable organisms. Chlorhexidine mouth rinse and dentifrices produced strong immediate antimicrobial effects, but after 1 or 6 h, the proportion of viable organisms in 9-h-old plaques rebounded significantly with only chlorhexidine mouth rinse retaining significant efficacy. Seventy-two-hour-old plaques were less susceptible to antimicrobials, although dentifrices appeared more effective after 6 h than initially, whereas efficacy of chlorhexidine rinse continued to drop with time posttreatment. Conclusions: The proposed method holds promise for assessment of both immediate and retained antimicrobial actions of oral treatments against dental plaque in vivo.